Analysis of the prevalence of dyslipidemia in individuals with HIV and its association with antiretroviral therapy - Limas,Talita Gabriela de (2014)
IntroductionAntiretroviral therapy (ART) has been used to treat large numbers of patients living with human immunodeficiency virus (HIV) infection. Lipid disorders are often observed in these patients, and include elevations in total cholesterol (TC) and triglycerides (TG).MethodsA cross-sectional study was performed using 333 patient records from the Regional Hospital of São José Doutor Homero de Miranda Gomes (HRSJHMG). The study population consisted of patients with HIV who were under medical follow up, either on or off drug treatment. The data were entered into Excel and exported to SPSS 16.0 for analysis using chi-square testing. We used prevalence ratios as the measure of association.ResultsLipid abnormalities were observed in 78.9% of individuals who received ART. Of the 308 subjects on ART, 59.1%, 41.9%, and 33.1% had TG, TC and low-density lipoprotein (LDL) abnormalities, respectively. The prevalence of LDL changes was 2.57-fold higher in individuals who had been using ART for more than 12 months, compared to those using ART for 6 to 12 months.ConclusionsHIV patients showed a significant increase in the association between TC and TG levels and the use of ART. In particular, changes in TC, LDL and TG were greater in individuals who had received ART for over more than 12 months.